Expression of DUSP4 transcript variants as a potential biomarker for colorectal cancer - Varela, Tatiana (2020)
Aim: To provide novel data on the expression of DUSP4 transcripts in colorectal cancer (CRC) tissues and to explore their potential as biomarkers. Materials & methods:DUSP4 transcripts expression was determined by quantitative real-time PCR in tissues from 28 CRC patients. Their association with clinicopathological factors and survival analysis was performed. Data from 380 CRC patients available at The Cancer Genome Atlas project were also analyzed. Results: All transcripts were overexpressed in CRC tissues. Variant X1 was the most upregulated and associated with KRAS mutations and poorly differentiated tumor. Overexpression of DUSP4 transcripts could distinguish all tumor stages from normal tissues. Similar results were found in The Cancer Genome Atlas cohort. Conclusion:DUSP4 transcripts have the potential to serve as diagnostic biomarkers for CRC, particularly variant X1.